(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
This study was conducted in a private orchard at Abu Al Khasib area in Basra province – Iraq, during the growing season (2013), to evaluate six cultivars of Ziziphus spp. Plant, phenologically and physiologically. The results confirmed a difference among the cultivars in some phenological characteristics, and a similarity in others. While in physiological characteristics, and a similarity in others. While in physiological characteristics the study showed a significant superiority of the Toffahi cultivar in its length, diameter and weight of fruits (4.00 cm, 3.26 cm and 7.30 g.) respectively and in its fruit dry weight percentage (42.38 %), while the Hindi cultivar was superior in the T.S.S., water content and phenols percentages (17.22, 67.36 and 2.21 %) respectively. But the Laimoni cultivar was superior in leaf area, adjustable total acidity percentage and calcium pectate percentage (6.78 cm2, 0.81 % and 4.57%) respectively. While Bathri cultivar was significantly superior in total chlorophyll content (3.36 mg. 100-1 fresh weight). Whilst the rest of cultivars showed a variable differences among them.